(untitled) (Raparin Journal of Humanities (RJH), 2025)
Body language is one of the most important means of non-verbal communication between humans. Through physical movements, gestures, faces and body postures, we can convey their information and feelings effectively. This study entitled (Analysis of Body Language Based on the Theory of Speech Acts) has made a complete analysis of body language from the perspective of the theory of speech acts. According to the analytical description approach, the study mentions the relationship between body movements and linguistic acts based on Austin’s principles, body language as an integral part of human communication plays an important role in communicating intentions, this is the essence of speech act theory, although speech act theory is primarily designed to analyze spoken language. However, it can also be used to analyze nonverbal communication. Body language can be interpreted and analysed as a complete verbal act because body language as an active nonverbal communication system, as verbal communication, creates and conveys meaning independently. Thus, body language can, as a complete system of verbal actions, perform illocutionary acts and subjunctive actions and carry the same purpose of the functions of speech acts: (imposing laws, requests, promises, expressions, decisions), because every body movement, a sender uses as a purpose and affects the recipient; therefore, that body language can be analysed as a complete system of speech acts.